2013
DOI: 10.3174/ajnr.a3635
|View full text |Cite
|
Sign up to set email alerts
|

CT Imaging Correlates of Genomic Expression for Oral Cavity Squamous Cell Carcinoma

Abstract: BACKGROUND AND PURPOSE:Imaging correlates of genetic expression have been found for prognostic and predictive biomarkers of some malignant diseases, including breast and brain tumors. This study tests the hypothesis that imaging findings correlate with relevant genomic biomarkers in oral cavity squamous cell carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Likewise a missense change, p.T1010I (rs56391007, COSM707), in the MET gene was identified in one of our HPV-negative tumors. Although this change has been reported as a somatic mutation previously in other cancers [29,30], it has not been reported in the TCGA HNSCC dataset and is suspected to be a constitutional polymorphism in the individual from which this tumor was derived based on the variant frequency being within the range of 40-60 %. We were unable to acquire additional material (i.e.…”
Section: Mutation Profilingmentioning
confidence: 79%
“…Likewise a missense change, p.T1010I (rs56391007, COSM707), in the MET gene was identified in one of our HPV-negative tumors. Although this change has been reported as a somatic mutation previously in other cancers [29,30], it has not been reported in the TCGA HNSCC dataset and is suspected to be a constitutional polymorphism in the individual from which this tumor was derived based on the variant frequency being within the range of 40-60 %. We were unable to acquire additional material (i.e.…”
Section: Mutation Profilingmentioning
confidence: 79%
“…In paraganglioma, four studies found higher PET SUV-values for SDHx -mutated tumors [ 152 154 ] or SHDx and VHL -mutated tumors [ 155 ], relevant for heritability risk assessment. In head neck tumors, EGFR -expression was related to CT invasion, mass effect, size/volume [ 156 ] and lower capillary permeability on perfusion CT [ 157 ]. Additionally, 14 studies each reported on radiogenomic associations of 14 other malignancies, respectively (Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…tumor size, multifocality) of both MRI and CT in various malignancies. Results included the correlations of enhancement features with VEGF -expression in brain tumors (glioblastoma) [ 158 ] and head-neck tumors (oral cavity SCC) [ 156 ].…”
Section: Resultsmentioning
confidence: 99%
“…Multidetector computed tomography (CT) is among the most important examinations when diagnosing and staging oral and oropharyngeal cancers [2,3]. Tumor enhancement and the degree of mass effect on contrast-enhanced CT imaging reportedly correlate with genomic biomarkers that are potential drug targets [4]. Although a direct endoscopic examination can accurately evaluate tumors on the mucosal surface, the submucosal tumor extension and vascularity cannot be evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Although a direct endoscopic examination can accurately evaluate tumors on the mucosal surface, the submucosal tumor extension and vascularity cannot be evaluated. Therefore, CT is essential for evaluating head and neck cancers, and pretreatment CT has significantly improved the long-term management of and therapeutic strategy for patients with oral cavity cancers [1,4]. However, the CT image quality in the oral cavity often suffers from artifacts caused by metallic materials [5].…”
Section: Introductionmentioning
confidence: 99%